2001
DOI: 10.2337/diabetes.50.11.2419
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Variant of Glutamine

Abstract: Glutamine:fructose-6-phosphate amidotransferase (GFAT) is the rate-limiting enzyme of the hexosamine synthesis pathway. Products of this pathway have been implicated in insulin resistance and glucose toxicity. GFAT1 is ubiquitous, whereas GFAT2 is expressed mainly in the central nervous system. In the course of developing a competitive reverse transcriptase-polymerase chain reaction assay, we noted that GFAT1 cDNA from muscle but not from other tissues migrated as a doublet. Subsequent cloning and sequencing r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
27
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 29 publications
1
27
3
Order By: Relevance
“…GlcN-6-P accumulation would be predicted to have the greatest impact on kinetic measurements at the Fru 6-phosphate site. In this study, the K m measured for Fru-6-P was at least an order of magnitude lower than from previous reports, whereas the K m for L-Gln was similar to previous reports with mammalian GFAT (10,12,13,27,28). In our studies, the K m for Fru-6-P and the K i for GlcN-6-P were roughly equivalent.…”
Section: Discussioncontrasting
confidence: 52%
See 4 more Smart Citations
“…GlcN-6-P accumulation would be predicted to have the greatest impact on kinetic measurements at the Fru 6-phosphate site. In this study, the K m measured for Fru-6-P was at least an order of magnitude lower than from previous reports, whereas the K m for L-Gln was similar to previous reports with mammalian GFAT (10,12,13,27,28). In our studies, the K m for Fru-6-P and the K i for GlcN-6-P were roughly equivalent.…”
Section: Discussioncontrasting
confidence: 52%
“…Huynh et al (10) reported the characterization of rat liver GFAT, and Milewski et al (8) reported the biochemical properties of the Candida enzyme, which exhibits similarities to the mammalian forms. Recent descriptions of the GFAT1 isoform, GFAT1Alt, demonstrated that GFAT1 and GFAT1Alt differ in their sensitivity to inhibition by UDP-GlcNAc (11,12). These studies agree that feedback regulation by the pathway end product, UDP-GlcNAc, is a common feature of all mammalian GFATs studied to date, unlike the bacterial forms (13,14).…”
supporting
confidence: 71%
See 3 more Smart Citations